Fever in the Neurointensive Care Unit - Chavali, Siddharth; Tripathi, Manjari; Rajagopalan, Vanitha (Journal of Neuroanaesthesiology and Critical Care, 2019)
Fever occurs commonly in patients admitted to the neurocritical care unit. An increase in the body temperature is known to have deleterious effects on patients with acute nervous system injury and in most cases is associated with an increase in mortality and morbidity of these patients. There are multiple causes of fever in these patients. Due to the potentially devastating effects of fever in patients with cerebral diseases, it warrants treatment in every case. In all patients with acute cerebral damage, treatment of fever and maintenance of euthermia is important to obtain a better functional recovery and to limit any further secondary insult to the brain. This review highlights the etiology and pathophysiology of fever in neurocritical care unit patients, the effects on various organ systems and associated systemic complications, and the evaluation and different therapeutic options available for the management of fever in this patient subset.
Keywords: fever; hyperthermia syndromes; neurointensive care